The Effect of Educational Intervention Based on the Theory of Planned Behavior in Promotion of Oral Health Behaviors in Pregnant Women of Rafsanjan City, Kerman, Iran - Zahra Farzaneh; Zahra Asadollahi; Mohammad Asadpour; Zohre Rahaei; farzaneh sardari (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Introduction: Theory of planned behavior can provide a framework for intervention to understand how to prevent health problems. The aim of this study was to determine the effect of training intervention based on the theory of planned behavior in promoting oral health behavior of pregnant women who visit health care centers of Rafsanjan. Methods: In this educational intervention trial, 100 pregnant women in Rafsanjan were selected by multi-stage sampling in 2016. Initially, four centers were randomly selected, followed by two centers selected as intervention groups and two centers as control groups. Data were collected using a three-part researcher-made questionnaire, that were completed by pregnant women in two periods, ie, before and three months after the intervention. Quantitative data were presented as mean ± SD and qualitative data as n (%). First, the homogeneity of the two groups was examined using an independent t-test and chi-square test. Data were analyzed with SPSS 18. The significance level of all tests was considered to be 0.05. Results: Findings showed that there was no statistically significant difference between the demographics of the two groups (p> 0.05). After the implementation of the program, the mean score of intervention in all constructs of the theory of planned behavior model was significant between the control and intervention groups (p < 0.001). Following the educational program, the oral health behavior of pregnant women increased in the intervention group (3.72 ± 4.22) which was significantly higher than the control group (1.48 ± 2.58) (p < 0.001). Conclusion: The results of this study showed that educational interventions can focus on the subjective norm which had fruitful results in the field of oral health. This theory can be used as an appropriate model for oral health promotion programs.